Public High School Students' Rationale of Food Choices and its Implication to Their Health Decisions and Literacy - MTTE, Sarah I. Obsequio-Namoco (Pakistan Journal of Nutrition, 2016)
Vast information on health literacy is widely available with the emergence of media accessibility. However, do the adolescents effectively utilize this information especially in their choice of food to eat? Adolescence is a vital stage in the growing up years because it is the period of physical, psychological and social maturing from childhood to adulthood, hence, optimum health is imperative. These adolescents spend most of their waking up hours at school. Therefore, educators play a vital role in connecting the gap. This study involved 1364 public high school students from the seven National High Schools of East II District in Cagayan de Oro City. The researcher surveyed on the available snack items sold among school canteens, the prevalent food bought by students and their reasons for buying such foods. It was found out that the food frequently consumed by students do not meet the minimum required energy and nutrient intake for their age and that price and palatability were the primary criteria for food choice. The nutrient value of the food is the least factor that students consider. This paper discusses the recommendations on the need to integrate the basic health information to make appropriate health decisions into the instruction.